2001
DOI: 10.1111/j.1747-7379.2001.tb00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants, Natives and Social Assistance: Comparable Take-Up under Comparable Circumstances

Abstract: Are immigrants on welfare because they are more likely to be eligible or because they are more likely to claim benefits for which they are eligible? The answer is politically important, but because most current research on immigration and welfare is based on data from the United States, the answer is difficult due to the complexities of the transfer system which make eligibility determinations difficult. In Germany, by contrast, eligibility for the main cash transfer program, Sozialhilfe (Social Assistance), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 10 publications
1
43
1
Order By: Relevance
“…Hansen and Lofstrom (2003) analyze the same issue for Sweden and find that migrants do use welfare programs significantly more than natives and that such a difference remains even after controlling for observable characteristics. On the other side of the spectrum of possible results, Castronova, Kayser, Frick, and Wagner (2001) find that any additional welfare dependency of migrants in Germany disappears once conditioning on a rich enough set of observable characteristics, a result that is also confirmed by Riphahn (2004). Bratsberg, Raaum, and Roed (2007) show that migrants in Norway are net users of the welfare state, with adverse consequences on their labour market performance.…”
Section: Introductionsupporting
confidence: 63%
“…Hansen and Lofstrom (2003) analyze the same issue for Sweden and find that migrants do use welfare programs significantly more than natives and that such a difference remains even after controlling for observable characteristics. On the other side of the spectrum of possible results, Castronova, Kayser, Frick, and Wagner (2001) find that any additional welfare dependency of migrants in Germany disappears once conditioning on a rich enough set of observable characteristics, a result that is also confirmed by Riphahn (2004). Bratsberg, Raaum, and Roed (2007) show that migrants in Norway are net users of the welfare state, with adverse consequences on their labour market performance.…”
Section: Introductionsupporting
confidence: 63%
“…Kaushal and Kaestner (2005) found that the Personal Responsibility and Work Opportunity Reconciliation Act generated fear among migrant families and caused lower participation rate in health insurance enrolment. Castronova, et al (2001) found that migrants were more likely than native Germans to receive welfare, not only because migrants were more likely to be eligible, but also because they were more likely to claim their benefits when they were eligible. However, they also found that this greater propensity to take up benefits was not really related to migrant status.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has compared the take-up rate of migrant groups and natives (Hansen and Lofstrom, 2003;Castronova, et al, 2001;Hu, 1998;Borjas, 2002;Hao and Kawano, 2001;Currie, 2000) and among different migrant groups (Borjas and Hilton, 1996; Davies and Greenwood, 1997; Davies, 1997;de Silva, 1997). Currie (2004) concludes that while migrants are more likely to be eligible for welfare, they are less likely to take it up, other things being equal.…”
Section: Introductionmentioning
confidence: 99%
“…As with the U.S. and the Swedish, Castronova et al (2001) motivate their analysis of the take-up of welfare payments by immigrants in Germany with reference to the higher rate of take-up among this group relative to natives. They quote earlier research as showing that immigrants in Germany were 3.7 times more likely to be in receipt of benefits relative to natives (Frick et al, 1999).…”
Section: Germanymentioning
confidence: 99%